Systematic search for local-search SAT heuristics - Burnett, Andrew W.; Parkes, Andrew J. (2016)
Heuristics for local-search are a commonly used method of improving the performance of algorithms that solve hard computational problems. Generally these are written by human experts, however a long-standing research goal has been to automate the construction of these heuristics. In this paper, we investigate the applicability of a systematic search on the space of heuristics to be used in a local-search SAT solver.